Biological Effects of Manganese Oxide Nanoparticles after Peroral Intake - N.V. Zaitseva; M.A. Zemlyanova; V.N. Zvezdin; T.I. Akafieva (Journal of Pharmacy and Nutrition Sciences, 2013)
Nanodispersed manganese oxide is a unique substance with a high application potential in nanoelectronics and nanooptics. The scientific literature contains little information about the biological effects and toxic action of this substance after it enters a human body. The biological effects were studied in Wistar rats after intragastric administration of manganese oxide for 30 days. The effects included loss in the body mass, activation of oxidation processes (increased level of lipid hydroperoxides, MDA in the blood serum), decrease in the antioxidant activity (inhibited antioxidant activity in the blood serum), damaged hepatocyte membranes (higher serum AST and ALT levels), and protein synthesizing liver function abnormalities (low albumins, high gamma globulins in the blood serum).